Kajian Teologis Praktek Sakramen Perjamuan Kudus - Andrian, Tonny (Sekolah Tinggi Teologi Kharisma, 2021)
The author conducts research on the theological study of the practice of the communion of the church in today's era so that it can find the implications of the meaning in holy communion. The research used is a literature analysis approach that uses various relevant literature sources. The study of Holy Communion reminds us of the importance of fellowship with fellow members of the body of Christ. The Sacrament of Holy Communion has been a part of the life of the Church since the time of the Lord Jesus until now. Until now, the sacrament of the Lord's Supper is still an interesting subject. In this discussion, Paul's teachings on the Sacrament of Holy Communion will be described to contribute to the administration of the sacrament. Holy Communion in the Lord's Churches today. Then followed by a reflection for the practice of Holy Communion today: What is the significance of the theological dimension in the practice of Holy Communion today? The hadil of this paper will be produced with practical tips for incorporating and presenting the theological dimension in the practice of the Lord's Supper today.Penulis melakukan penelitian terhadap kajian teologis praktek perjamuan kudus gereja masa kini sehingga dapat menemukan implikasi makna dalam Perjamuan Kudus. Penelitian yang digunakan adalah pendekatan analisis pustaka yang menggunakan berbagai sumber pustaka relevan. Kajian Perjamuan Kudus mengingatkan tentang pentingnya persekutuan dengan sesama anggota tubuh Kristus. Sakramen Perjamuan Kudus sudah menjadi bagian dari kehidupan Gereja sejak zaman Tuhan Yesus sampai sekarang. Hingga saat ini sakramen Perjamuan Kudus masih menjadi bahasan menarik. Dalam bahasan ini akan diuraikan ajaran Paulus tentang Sakramen Perjamuan Kudus untuk memberi kontribusi bagi pelaksanaan Perjamuan Kudus di Gereja-Gereja Tuhan pada masa kini. Kemudian disambung dengan refleksi untuk praktik Perjamuan Kudus di masa sekarang: Apa signifikansi dimensi teologis dalam praktek Perjamuan Kudus menurut tulisan Rasul Paulus. Hasil tulisan ini akan dihasilkan dengan pelbagai tips praktis untuk memasukkan dan menampilkan dimensi teologis dalam praktik Perjamuan Kudus masa kini.